2021
DOI: 10.12659/ajcr.933460
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus Complicated by Hemolysis, Elevated Liver Enzymes, and Low Platelet Count After Decreased Need for Insulin: 2 Cases

Abstract: Case series Patient:— Final Diagnosis: Acute fatty liver of pregnancy • HELLP syndrome Symptoms: Decrease in insulin dosage for gestational diabetes mellitus Medication: — Clinical Procedure:— Specialty: Obstetrics and Gynecology Objective: Unusual clinical course Background: When a woman becomes pregnant, the placenta produces human placental lactogen (hPL). The anti-insulin effect of hP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…As hPL is produced by the placenta until delivery, insulin requirements in patients with GDM generally increase, but in exceptional situations, some cases may lead to a decrease in this insulin requirement. Kawarai et al 6 retrospectively examined data from patients with GDM who received insulin and gave birth between April 2019 and March 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As hPL is produced by the placenta until delivery, insulin requirements in patients with GDM generally increase, but in exceptional situations, some cases may lead to a decrease in this insulin requirement. Kawarai et al 6 retrospectively examined data from patients with GDM who received insulin and gave birth between April 2019 and March 2020.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients, insulin dosage is decreased, but no studies to date have reported perinatal prognosis in the context of reduced insulin requirements during pregnancy. 6 Some recent findings allow us to better explain the pathophysiology of GDM. Chemerin is one such example.…”
Section: Introductionmentioning
confidence: 99%
“…Como o hPL é produzida pela placenta até o parto, as necessidades de insulina em pacientes com DMG geralmente aumenta, mas em situações de excessão, alguns casos podem cursar com uma diminuição desta necessidade insulínica. Kawarai et al 6 examinaram, retrospectivamente, dados de pacientes com DMG que receberam insulina e deram à luz entre abril de 2019 a março de 2020.…”
Section: Discussionunclassified
“…Em alguns pacientes, a dosagem de insulina é diminuída, mas nenhum estudo até o momento, relatou o prognóstico perinatal no contexto de necessidades reduzidas de insulina durante a gravidez. 6 Algumas descobertas recentes permitem explicar melhor a fisiopatologia do DMG. A quemerina é um destes exemplos.…”
Section: Introductionunclassified